Ultrasound-Assisted Extractions for Improving the Recovery of Phenolics and Charantin from Bitter Melon and for Increasing the Antioxidant, Antidiabetic and Anti-Obesity Activities of Its Extracts - Jin Ju Lee; Kyung Young Yoon (Polish Journal of Food and Nutrition Sciences)
Bitter melon is rich in bioactive compounds and has a significant potential for commercial use as a functional food material. Its bioactive compound-rich extract was prepared using probe- or bath-type ultrasound-assisted extraction (UAE) with 60% ( v/v ) ethanol or distilled water. The composition and bioactivity of the extracts prepared using UAE was compared with those obtained by conventional extraction methods, such as autoclave extraction, ethanol extraction, and hot-water extraction. Although the yield of the autoclave extraction was the highest, the extracts obtained using UAE and aqueous ethanol exhibited a higher total phenolic content, antioxidant activity, antidiabetic activity (α-amylase and α-glucosidase inhibitory activities), and pancreatic lipase inhibitory activity than the conventional extracts. In particular, UAE with probe system and aqueous ethanol (UAE-P-E) was effective for extracting bioactive compounds, such as phenolics (total phenolic content of 18.73 mg GAE/g extract) and charantin (28.56 mg/g extract). Among all extracts, this prepared by UAE-P-E showed the highest DPPH radical scavenging activity (IC50 of 0.55 mg/mL), ferric reducing antioxidant power (250.5 μmol/g extract), and pancreatic lipase inhibitory activity (76.38% at a concentration of 3.0 mg/mL). These results suggest that bioactive compound-rich extracts from bitter melon obtained using UAE, especially UAE-P-E, are expected to have high application potential as a functional food material, and are also expected to be used as natural antioxidant, antidiabetic, and anti-obesity agents.